CALCULATIONS OF EM INTERACTIONS WITH BIOLOGICAL TISSUE: MAGNETIC RESONANCE IMAGING AT ULTRA HIGH FIELD - Ibrahim, Tamer S.; Ibrahim, Tamer S. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A finite difference time domain model is developed to simulate a TEM resonator for high frequency clinical magnetic resonance imaging applications. The coil-head electromagnetic interactions and their effects on the SAR in biological tissue are presented. The TEM resonator and the newly developed 18-tissue anatomically detailed human head are treated together as a single system. This is done through all the step of the model including excitation and numerical tuning. The treatment of the resonator and the head as a single system and the geometrical modeling of all the coil components including coaxial rods, shield, circular rings, and the excitation source(s), accurately account for the electromagnetic interactions between the coil and the tissue. As a result, close agreement was achieved between the FDTD results and MRI images obtained at 8 Tesla. The results show strong electromagnetic interactions between the coil in general, the excitation source(s) in particular, and the human head. As such, it is shown that the specific absorption rate (SAR) values are largely dependent on these interactions. Comparisons of linear, 2-port quadrature, and 4-port excitations with respect to SAR values were performed at 340 MHz (8 Tesla). The analysis reveals the advantages of using 4-port drive over the conventional 2-port quadrature excitation especially in reducing the SAR peak values